2022
DOI: 10.1038/s41598-022-07730-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic models characterize seizure propagation and the effects of epilepsy surgery in individualized brain networks based on MEG and invasive EEG recordings

Abstract: Epilepsy surgery is the treatment of choice for drug-resistant epilepsy patients. However, seizure-freedom is currently achieved in only 2/3 of the patients after surgery. In this study we have developed an individualized computational model based on MEG brain networks to explore seizure propagation and the efficacy of different virtual resections. Eventually, the goal is to obtain individualized models to optimize resection strategy and outcome. We have modelled seizure propagation as an epidemic process usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(63 citation statements)
references
References 119 publications
(169 reference statements)
7
55
0
1
Order By: Relevance
“…Using the iEEG data for the modeling cohort patients, we fit γ and ρ to reproduce the iEEG-recorded seizure propagation patterns with the ESSES-modeled seizures, setting the resection area was used as the epidemic seed (see 5.5 and Supp. section 5.2 for more details) [30,32]. The degree of similarity between the ESSES and iEEG seizures was measured with the goodness-of-fit C(ρ, γ) as defined in eq.…”
Section: Seizure Propagation As An Epidemic Spreading Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the iEEG data for the modeling cohort patients, we fit γ and ρ to reproduce the iEEG-recorded seizure propagation patterns with the ESSES-modeled seizures, setting the resection area was used as the epidemic seed (see 5.5 and Supp. section 5.2 for more details) [30,32]. The degree of similarity between the ESSES and iEEG seizures was measured with the goodness-of-fit C(ρ, γ) as defined in eq.…”
Section: Seizure Propagation As An Epidemic Spreading Processmentioning
confidence: 99%
“…Although such models ignore the underlying bio-physical processes that lead to seizure generation and propagation, they do describe the basic rules that govern spreading processes. In previous studies [30,32], we found that epidemic spreading models could reproduce stereotypical patterns of seizure propagation as recorded via invasive electroencephalography (iEEG) recordings . Moreover, once fitted with patient-specific data, ESSES could identify alternative resection strategies, either of smaller size or at a different location than the actual surgery [24,30].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations